Optimasi Keuntungan Produksi Olahan Salak Pondoh di Desa Wisata Pulesari dengan Metode Integer Linear Programming (Unnes Journal of Mathematics, 2022)
This study aims to determine the composition of the amount of each type of processed salak pondoh that must be produced so as to maximize production profits in Pulesari Tourism Village. The data obtained in this study are primary data and secondary data. The results of calculations that have been carried out using Integer Linear Programming obtained an optimal profit of Rp4,874,788.00 while after the pandemic showed an optimal profit of Rp2,461,555.00. The difference in calculations using the Integer Linear Programming method with the calculations made by Processed Salak Pondoh before the pandemic was Rp250,396.00 while after the pandemic is Rp132,597.00 per day, and this shows that the production profit obtained by the Integer Linear Programming method is more optimal than the partner calculation. processed bark.